Official Souvenir Postal (Charles W. Goldsmith, Agent for the United States, the Issabella, 48 Van Buren St. Chicago.)
Portrait of Christopher Columbus and Thwe Fisheries building noted on lithograph by American Lithographing Co. N.Y. Litho., series no. 1, twelve designs old style postcard with no split back for text and address.